Treatment With High-Hydrostatic Pressure, Activated Film Packaging With Thymol Plus Enterocin AS-48, and Its Combination Modify the Bacterial Communities of Refrigerated Sea Bream (Sparus aurata) Fillets - Ortega Blázquez, Irene; Grande Burgos, María J.; Pérez-Pulido, Rubén; Gálvez, Antonio; Lucas, Rosario (Frontiers in Microbiology, 2018)
The aim of this study was to determine the impact of activated plastic films with thymol and enterocin AS-48 and high-hydrostatic pressure (HP) treatment on the bacterial load and bacterial diversity of vacuum-packaged sea bream fillets under refrigerated storage for 10 days. The activated film and the HP treatment reduced aerobic mesophiles viable counts by 1.46 and 2.36 log cycles, respectively, while the combined treatment achieved a reduction of 4.13 log cycles. HP and combined treatments resulted in longer delays in bacterial growth. Proteobacteria were the dominant phyla in sea bream fillets. The relative abundance of Firmicutes increased by the end of storage both in controls and in samples treated by HP singly or in combination with the activated films. The predominant operational taxonomic units (OTUs) found at time 0 in control samples (Listeria, Acinetobacter, Pseudomonas, Enterobacteriaceae, Chryseobacterium) rapidly changed during storage (with an increase of Vibrio, Photobacterium, and Shewanella together with Cloacibacterium and Lactobacillales by the end of storage). The activated film and the HP treatment induced drastic changes in bacterial diversity right after treatments (with Comamonadaceae, Methylobacterium, Acidovorax, and Sphingomonas as main OTUs) and also induced further modifications during storage. Bacterial diversity in activated film samples was quite homogeneous during storage (with Vibrio, Photobacterium, and Shewanella as main OTUs) and approached control samples. HP treatments (singly or in combination with activated films) determined a high relative abundance of Acinetobacter (followed by Pseudomonas and Shewanella) during early storage as well as a higher relative abundance of lactic acid bacteria by the end of storage. The results indicate that the complex dynamics of bacterial populations in the refrigerated sea bream fillets are markedly influenced by treatment and antimicrobials applied.